Historiando la familia esclava en Cuba - Barcia Zequeria, María del Carmen (El Colegio de México, A.C., 2025)
This article studies the issue of the family, an essential element of any social construct and one that has been addressed from many different historical angles, alongside that of slavery, which has been distorted, reviled and even denied under a supposedly academic cover. This representation has meant that myths continue to be repeated as absolute truths that the reality of these and other historical studies have worked to deconstruct. This article reveals the characteristics taken on by the institution in Cuba, from the perspectives of  consanguinity and affinity. Its sources combine legislation and archival documents.